An Introduction to Radical Biocracy: A relational, autonomous approach to decision-making towards emergent and symbiotic design - Victor Udoewa (Design Science)
Any system health work must look at decision-making because decisions propagate throughout a system, shaping system dynamics. Usually, human decision-making is conducted from an individualist, objectivist perspective. What happens when we use an approach based on the radical relationality of Radical Participatory Design and Relational Design? This is the fourth paper in a series of papers which introduced Radical Participatory Design in the first two papers and Relational Design in the third paper. In this fourth paper, we explore the decision-making dynamics in Radical Participatory Design and Relational Design projects.